Expedient Hydrofunctionalisation of Carbonyls and Imines Initiated by Phosphacyclohexadienyl Anions. Issue 17 (19th June 2021) - Margeson, Matthew J.; Seeberger, Felix; Kelly, John A.; Leitl, Julia; Coburger, Peter; Szlosek, Robert; Müller, Christian; Wolf, Robert
Abstract: The ability of phosphacyclohexadienyl anions [Li(1‐R‐PC5 Ph3 H2 )] [R=Me (1 a ), n Bu (1 b ), t Bu (1 c ), Ph (1 d ) and CH2 SiMe3 (1 e )] to initiate hydrofunctionalisation reactions was investigated and compared with simple, commercially available compounds, such as LiO t Bu, KO t Bu and n BuLi. All compounds are expedient catalysts for the hydroboration of a wide scope of substrates, ranging from aldehydes to imines and esters. In the hydroboration of carbon dioxide, however, only our system was observed to efficiently produce the desired methanol equivalents. Abstract : Anion catalysis : Hydrofunctionalisations of various substrates, including, imines, esters and CO2 are effectively initiated by lithium phosphacyclohexadienyl compounds. High selectivities and excellent TOFs were found, rivalling those of previously reported organic and alkoxide anions.